2007
DOI: 10.1021/ja0749744
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Stability and Biological Functionalities of Quantum Dots via Compact Multifunctional Ligands

Abstract: We have designed and synthesized a series of modular ligands based on poly(ethylene glycol) (PEG) coupled with functional terminal groups to promote water-solubility and biocompatibility of quantum dots (QDs). Each ligand is comprised of three modules: a PEG single chain to promote hydrophilicity, a dihydrolipoic acid (DHLA) unit connected to one end of the PEG chain for strong anchoring onto the QD surface, and a potential biological functional group (biotin, carboxyl, and amine) at the other end of the PEG. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
429
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 485 publications
(436 citation statements)
references
References 34 publications
6
429
0
1
Order By: Relevance
“…The difference of the QYs of the two dispersions reveals that QD deterioration occurred during ligand exchange, as reported previously. 11,[24][25][26][27][28] Ligand exchange changes the chemical and physical states of atoms on the QD surface, and causes QYs to decrease. 29 The QY of InP/ZnS-MPA@TMAS was similar to that of the InP/ZnS-MPA QD dispersion, while the QY of InP/ZnS-DDT@PMMA was much lower than that of the dispersion of InP/ZnS-DDT QDs.…”
Section: Resultsmentioning
confidence: 99%
“…The difference of the QYs of the two dispersions reveals that QD deterioration occurred during ligand exchange, as reported previously. 11,[24][25][26][27][28] Ligand exchange changes the chemical and physical states of atoms on the QD surface, and causes QYs to decrease. 29 The QY of InP/ZnS-MPA@TMAS was similar to that of the InP/ZnS-MPA QD dispersion, while the QY of InP/ZnS-DDT@PMMA was much lower than that of the dispersion of InP/ZnS-DDT QDs.…”
Section: Resultsmentioning
confidence: 99%
“…-COOH, -OH, -NH 2 (Hoshino et al 2004;Susumu et al 2007;, or CdTe and, for instance, a mixture of MPA and aminoethylthiol (Wuister et al 2003).…”
Section: Particle Functionalization (A) Chemical Functional Groupsmentioning
confidence: 99%
“…Surface oxidation and pH value during storage are two prominent factors that influence QD stability. For extended stability in basic buffers, dihydrolipoic acid (DHLA) could be attached to the QD surface via a PEG linkage [18]. The hydroxylcoated QDs prepared by Kairdolf et al showed stability under both basic and acidic conditions, with minimized nonspecific binding [19].…”
Section: Quantum Dotsmentioning
confidence: 99%